Twenty years of forest management certification in the tropics: Major trends through time and among continents - Ehrenberg-Azcárate, Francisco; Peña-Claros, Marielos (Forest policy and economics, 2020)
For over 20 years, forest management certification—particularly that of the Forest Stewardship Council (FSC)—has been promoted as a way to manage tropical natural forests responsibly. To shed light on the current and historical trends of this market-driven, forest governance intervention, we obtained information from the public summaries of evaluation reports belonging to 543 forest management units (FMUs) located in the tropics and covering 20 years of certification, from 1995 until 2016. Additionally, we analyzed 4621 corrective action requests (CARs) issued by third-party auditors during the initial certification attempts of companies and groups managing tropical natural forests to increase our understanding of the nature of problematic management issues and their evolution across different regions. By the end of 2016, most of the certified forest area was located in Africa, followed by the Americas and Asia. The tropics experienced a period of stagnation regarding certified area growth during the last decade, partly as a consequence of a pantropical wave of certificate terminations that started in 2008, having a severe impact in the Americas and a moderate one in Asia and Africa. Our results suggest that FMUs that remain certified for relatively more extended periods are more resilient against external economic pressures. One implication is that managers and policymakers should develop mechanisms to encourage long-term certification, particularly among small-holders as the amount of certified area managed by groups (i.e., communities and groups of small companies) has decreased throughout the last decade. We highlight the importance of looking into the temporal and regional dynamics to get a broader perspective of FSC certification at the tropical level. •In 2016, most of the certified forest area in the tropics was located in Africa.•The area of certified forest has not significantly increased since 2008.•The economic crisis reduced the number of certified companies in the tropics.•Resilience towards external pressures increases with time since first certification.•Issues faced by FMU in the tropics change through time and with region.